(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The objective of this article was to present a writing exercise on the bodily and cognitive sensations that emerged in the presentations and in the appreciation of the video recording (recently revisited) of the dance show “HOW TO (DE)CONSTRUCT A MALE?”. The manifesto "Homens Libertem-se" inspired the creation of the show that addressed the issue of structural male chauvinism, and two of the nine scenes were chosen for the description. This exercise dialogued with the research genre called performative autoethnography and highlighted the self in the writing, presenting body as an epistemological source of investigation and recognizing the complexity of the local culture in which the author is inserted.